Confronting Community Gun Violence Through Research Translation: A Case Study of Challenges and Facilitators - Noorman, Kaylee (American journal of criminal justice, 2025)
In recent years, gun violence has surged in many cities along with increasing demands for effective intervention and prevention. Researcher-practitioner partnerships (RPPs) have been identified as a promising practice to effectively respond to a particular community’s gun violence with appropriately aligned intervention and prevention programs. However, recently, numerous sources have called for RPPs to include the perspectives of those with lived experiences as part of the RPP model, yet inclusion of these voices can present unique challenges for research translation. This case study contributes to the budding understanding of these specific RPPs by documenting the experienced procedures and challenges of a local community-engaged RPP. Specifically, we describe the development of this partnership, the research partner’s activities during the planning phase of this partnership, and, primarily, outline and assess the challenges encountered through the inclusion of community partners and voices during this phase and discuss the impact of these challenges on project progress. Documented challenges included weighing community perceptions of crime versus empirical data, putting the “cart before the horse,” and managing expectations. These challenges contributed to goals, roles, and expectations being misaligned with the focus of the partnership, competing priorities and recommendations for implementation strategies, and resistance to research translation. We conclude with tangible recommendations for the initiation of a community-engaged approach to RPPs, focusing on how to preemptively circumvent or more adeptly navigate these distinctive challenges.